Teaching about teaching and instruction on instruction: a challenge for health sciences library education. - Gay Detlefsen, Ellen (Journal of the Medical Library Association, 2012)
Objective: This is a review of the master's-level curricula of the fifty-eight America Library Association-accredited library and information science programs and iSchools for evidence of coursework and content related to library instruction. Special emphasis is placed on the schools and programs that also offer coursework in medical or health sciences librarianship. Methods: Fifty-eight school and program websites were reviewed. Course titles and course descriptions for seventy-three separate classes were analyzed. Twenty-three syllabi were examined. Results: All North American library education programs offer at least one course in the general area of library instruction; some programs offer multiple courses. No courses on instruction, however, are focused directly on the specialized area of health sciences librarianship. Conclusions: Master's degree students can take appropriate classes on library instruction, but the medical library profession needs to offer continuing education opportunities for practitioners who want to have specific instruction for the specialized world of the health sciences.